Toosendanin and isotoosendanin suppress triple-negative breast cancer growth via inducing necrosis, apoptosis and autophagy. (5th January 2022) - Zhang, Jingnan; Yang, Fan; Mei, Xiyu; Yang, Rui; Lu, Bin; Wang, Zhengtao; Ji, Lili
Abstract: Toosendanin (TSN) and isotoosendanin (ITSN) are two natural triterpenoids isolated from Fructus Meliae Toosendan or Cortex Meliae. This study aims to observe the inhibition of TSN and ITSN on the growth of triple-negative breast cancer (TNBC) and the preliminary engaged mechanism. Cell viability assay showed that both TSN and ITSN had obvious cytotoxicity in a variety of tumor cells, and they had the best inhibitory effect on TNBC cells including MDA-MB-231, BT549 and 4T1. Propidium iodide (PI) staining results showed the increased number of necrotic MDA-MB-231 and 4T1 cells induced by TSN (20 nM) and ITSN (2.5 μM). Annexin V-FITC and PI double-staining results showed that TSN (20 nM) and ITSN (2.5 μM) induced cell apoptosis in both MDA-MB-231 and 4T1 cells. Moreover, TSN (20 nM) and ITSN (2.5 μM) induced the cleavage of pro-caspase-3 and pro-caspase-9, and decreased the expression of anti-apoptotic Bcl-xL in both MDA-MB-231 and 4T1 cells. Results from scanning electron microscope observation and detecting the expression of microtubule-associated protein 1 light chain 3B (LC3B) and Beclin 1 evidenced that TSN (20 nM) and ITSN (2.5 μM) induced autophagy in both MDA-MB-231 and 4T1 cells. TSN and ITSN decreased 4T1 xenograft tumor growth without inflicting toxicity on vital organs in mice. Collectively, this study shows that natural compound TSN and ITSN suppress TNBC growth via inducing necrosis, apoptosis and autophagy. TSN and ITSN could be promising drugs for TNBC treatment. Graphical abstract: Image 1 Highlights: TSN and ITSN suppress TNBC growth both in vivo and in vitro. TSN and ITSN induce TNBC necrotic death. TSN and ITSN induce TNBC apoptosis. TSN and ITSN induce TNBC autophagy.